Standing up for competition: Market concentration, regulation, and Europe's quest for a new industrial policy - Oscar Guinea; Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2019)
After the failed merger of Alstom and Siemens - the two giants of Europe's railway manufacturing sector - the French and the German governments presented a manifesto with a set of radical proposals designed to reshape EU industrial and competition policy. In an article addressed to all European citizens, the President of France, Emmanuel Macron, urged for reform of EU competition policy, to protect Europe from foreign competition[1]. MEP Guy Verhofstadt, the leader of the European liberals, supports similar claims that Europeans cannot compete with Chinese or American firms[2]. One of the Franco-German suggestions would empower the European Council to veto European Commission decisions on competition policy. French and German Ministers argue that Europe's competitiveness in manufacturing is in decline. Somehow weakening EU competition policy, the manifesto claims, will strengthen Europe's competitiveness. This argument is wrong. To be competitive, European firms need more not less competition. Measures to promote market competition in Europe should be at the front and centre of any future industrial policy. Unfortunately, the evidence shows that market competition in Europe is not rising but declining.
Keywords: 330